Relação entre variáveis de crescimento e o Índice de Qualidade de Dickson em mudas de Eucalyptus grandis W. Hill ex Maid e Pinus elliottii var. elliottii - Engelm - Binotto, Alexandre Francisco (2007)
The present work had for objective to verify the relation between growth variability and the interference Dickson Quality Index, to verify the efficiency relation of this /index in the quality indication on seedlings and to identify the behavior of the growth variable during the seedlings development cycle in trays with full and varied competition in Eucalyptus grandis W. Hill ex Maid and Pinus elliottii var. elliottii Engelm seedlings, in the forest nursery of the Universidade Federal de Saint Maria, RS. In this way, for both species, was installed a blank experiment in the greenhouse. The data collection for E. grandis had been to the 60, 75, 90, 105 and 120 days, after the seedling sprout and for P. elliotti to 25, 50, 75, 100, 125, 150, 175 days, after the seedling sprout (DAE). Each species were represented for two trays, being that in one of them was analyzed the diameter of the col (DIAM, in mm), the height of the aerial part (ALT, in cm), the leaf number (NF) (only for E. grandis), dry fitomass of leaves (MSF in gram/plant), dry fitomass of the col (MSC gram/plant), dry fitomass of the radicular system (MSR gram/plant); dry fitomass of the aerial part (MSPA gram/plant), gotten for the sum of MSF and MSC; total dry fitomass(MST), gotten for the sum of MSPA and MSR; the relation of the aerial part/radicular system (RPAR), gotten of the relation between MSPA and MSR; and the relation of the aerial part height /diameter of the col (RAD), gotten from the relation between ALT and DIAM, and the Dickson Quality Index (IQD), gotten from an equation involving the morphologic variable, previously cited, except the NF. For this tray, after each data collection was selected a parcel of seedlings for fitomassas attainment. One proceeded the rearrangement from the remaining seedlings, with the intention of verifying the interference that the seedlings would suffer, giving them a bigger luminosity and aeration. To the other tray were analyzed diameter of col DIAM, ALT, NF (for E. grandis), remaining during all the study, the total number of seedlings. Through statistical methods of Regression Analysis, Pearson Correlation and Pathy Analysis different combinations between the morphologic variables had been studied, with DAE and IQD, using as election criterion for the regression mathematical models: the biggest value of the adjusted determination coefficient (R ² aj), minor variation coefficient (CV%) and minor error average standard (Syx). Dry root Fitomass, was the more related variable with the IQD, however its not viable the attainment because its necessary the destruction of the plantt. The diameter of the col was the most propitious variable to indicate seedling quality, based in its bigger degree of Dickson relation Index(IQD). The varialble height just presented efficient to indicate seedling quality when analyzed together the diameter. The IQD was efficient to indicate seedling quality, therefore it was presented sufficiently related with the studied variables for E. grandis and P. elliotti. The variable col diameter was the one that presented greater relation after sprout, when compared with the seedling height, as much in trays with seedlings in full competition how much in varied competition, for both the studied species